The Language of Resistance in Wiji Thukul's Nyanyian Akar Rumput: A Critical Discourse Analysis - Apriliana, Milda (Lia Center of Research and Education, 2025)
This study aims to uncover the language strategies of resistance used by Wiji Thukul in his poem Nyanyian Akar Rumput through a critical discourse analysis approach. Data obtained from the poem's text as the primary source are analyzed using Fairclough's critical discourse analysis framework, which encompasses aspects of text, discourse practice, and social practice. The results of the study indicate that the symbol